Markers of Endothelial Dysfunction Are Attenuated by Resveratrol in Preeclampsia - Bueno-Pereira, Thaina Omia [UNESP]; Bertozzi-Matheus, Mariana [UNESP]; Zampieri, Gabriela Morelli [UNESP]; Abbade, Joelcio Francisco [UNESP]; Cavalli, Ricardo C.; Nunes, Priscila Rezeck [UNESP]; Sandrim, Valeria Cristina [UNESP] (MDPI, 2022)
Preeclampsia (PE) is characterized by great endothelial dysfunction, decreased nitric oxide (NO) bioavailability, and higher levels of arginase activity. In the present study, we investigated the potential modulatory effects of trans-resveratrol (RSV) on arginase and endothelial dysfunction biomarkers in endothelial cells exposed to plasma from patients with PE and healthy pregnant (HP) women, and umbilical arteries from patients with PE. Human umbilical vein endothelial cells (HUVECs) were incubated with pooled plasma from 10 HP or 10 PE pregnant women and RSV; umbilical arteries from patients with PE were incubated with RSV; intracellular NO and total reactive oxygen species (ROS) levels were assessed using a probe that interacted with these radicals; total arginase activity was evaluated measuring the urea produced; total antioxidant capacity was measured using the ferric reduction ability power (FRAP) assay; and endothelial dysfunction biomarkers were assessed using qPCR in endothelial cells and umbilical arteries. RSV increased NO levels and decreased total arginase activity in endothelial cells incubated with plasma from patients with PE. In addition, RSV increased total antioxidant capacity and downregulated endothelial dysfunction biomarkers, such as intercellular adhesion molecule-1 (ICAM-1), von Willebrand factor (vWF), and Caspase-3, (CASP-3), in endothelial cells and umbilical arteries from PE patients. RSV treatment positively modulated the L-arginine–NO pathway, decreased arginase activity, and increased antioxidant capacity, in addition to downregulating endothelial dysfunction biomarkers.
Keywords: arginase; endothelial cells; nitric oxide; oxidative stress; preeclampsia; resveratrol